Relevansi Peran Media Komunikasi Sosial Bagi Persekutuan dan Pengembangan Manusia Menurut Dokumen Communio Et Progressio - Alfons Seran; Evimawati Harefa; Meslina Halawa (Jurnal Magistra, 2024)
This article discusses the relevance of the role of social communication media for fellowship and human development according to the Communio et Progresio document. The use of social communication media is something that cannot be separated from human life today. The Church welcomes the development of social communication media with joy and views it as a gift from God. The Church wants to use social communication media as a means to build worldwide communion and develop human life. This article uses the library research method, which is a theoretical study, references and various scientific literature related to the research theme. The role of social communication media is very significant for humans to build relationships with each other quickly, share knowledge and information for human development and build solidarity throughout the world, specifically as a means of preaching the Gospel. However, here it is different, it has a negative impact on human life. Therefore, the Church through hierarchical authority supervises, controls and guides people so that people use social communication media wisely and wisely to build community and develop life.